Electrochemical Ceramic Membrane Reactors in Future Energy and Chemical Process Engineering. Issue 6 (25th April 2019) - Heddrich, Marc P.; Gupta, Sanchit; Santhanam, Srikanth
Abstract: Electrochemical ceramic membrane reactors (ECMRs) with their unique ability to efficiently couple electrical, chemical, and thermal energy sectors can be a large part of the transition toward renewable energies and defossilized economies. ECMRs utilize ceramic conductors to extract or distribute oxide ions or protons – directly controlled by an external electric current. This article gives an overview of ECMR properties along with the functionalities and advantages. For many reactions, e.g., the direct synthesis of ammonia, ECMRs are not available at the preferred temperature range of 300 – 550 °C. To evidence the possibility of such reactors, functional materials are reviewed. A simple thermodynamic methodology is proposed to determine the suitability of reactions for particular combinations of coupled energy sectors. Abstract : Electrochemical ceramic membrane reactors (ECMRs) can be used to efficiently couple electrical, chemical, and thermal energy sectors. An overview of ECMR functionalities and their benefits for future energy and chemical process systems is given. The suitability of reactions for bulk chemical production is examined with a simple thermodynamic method.